2014
DOI: 10.1039/c4cc03884c
|View full text |Cite
|
Sign up to set email alerts
|

Porous organic ligands (POLs) for synthesizing highly efficient heterogeneous catalysts

Abstract: We reported a universal route for synthesizing porous organic ligands (POLs) via solvothermal polymerization. The POLs were obtained quantitatively, showing high surface area, large pore volume, hierarchical porosity, and superior stability. The POL bearing a triphenylphosphine supported rhodium catalyst (Rh/POL-PPh3) exhibits high activity and excellent recyclability in 1-octene hydroformylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 47 publications
1
104
0
5
Order By: Relevance
“…For instance, Rh metalated porous organic ligand polymers of triphenylphosphine (POL-PPh 3 ) as heterogeneous catalysts exhibit not only comparable activities and selectivities to those of the homogeneous counterparts in olefin hydroformylations but also extraordinary recyclabilities [49]. It is also shown that the metalated (Fe and Mn) porous organic polymers (POPs) containing free-base porphyrin subunits by the condensation of a bis(phthalic acid)porphyrin with tetra(4-aminophenyl)methane [50] are very active catalysts in both olefin epoxidation and alkane hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rh metalated porous organic ligand polymers of triphenylphosphine (POL-PPh 3 ) as heterogeneous catalysts exhibit not only comparable activities and selectivities to those of the homogeneous counterparts in olefin hydroformylations but also extraordinary recyclabilities [49]. It is also shown that the metalated (Fe and Mn) porous organic polymers (POPs) containing free-base porphyrin subunits by the condensation of a bis(phthalic acid)porphyrin with tetra(4-aminophenyl)methane [50] are very active catalysts in both olefin epoxidation and alkane hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…The 504 h time onstream performance showed no apparent drop in activity and selectivity, demonstrating the excellent catalyst stability. The high l/b ratio of aldehydes may originate from the shape-selectivity imposed by the 0.7-1.5 nm micropores present in the Rh/POL-PPh 3 catalyst [25].…”
Section: Hydroformylation Of 1-dodecenementioning
confidence: 99%
“…POL-PPh 3 was prepared according to the method reported previously [25]. Rh/POL-PPh 3 and HRh(CO)(PPh 3 ) 3 /POL-PPh 3 catalysts were prepared, respectively.…”
Section: Preparations Of the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] We now hope to employ this polymer as as upporting ligand for palladium-catalyzed Suzuki-Miyaurac ross-coupling reactions.P OL-Ph 3 P is an ew type of three-fold cross-linked polymerbound phosphine [11] and can be prepared through solvothermalp olymerization of tris(p-vinylphenyl)phosphine in the absence of styrene and divinylbenzene (see Scheme1). Compared with polystyrene-supported phosphine,t his novelp hosphine possesses am uch higher Pc ontent ande nhances metal binding ability.…”
Section: Introductionmentioning
confidence: 99%